2011
DOI: 10.1186/1471-2466-11-5
|View full text |Cite
|
Sign up to set email alerts
|

Adherence with tobramycin inhaled solution and health care utilization

Abstract: BackgroundAdherence with tobramycin inhalation solution (TIS) during routine cystic fibrosis (CF) care may differ from recommended guidelines and affect health care utilization.MethodsWe analyzed 2001-2006 healthcare claims data from 45 large employers. Study subjects had diagnoses of CF and at least 1 prescription for TIS. We measured adherence as the number of TIS therapy cycles completed during the year and categorized overall adherence as: low ≤ 2 cycles, medium >2 to <4 cycles, and high ≥ 4 cycles per yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
73
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 17 publications
5
73
0
1
Order By: Relevance
“…In the context of a clinical trial setting, the patients' adherence is generally high, whereas in the real-world, rates of adherence and persistence rates are much lower and the efficacy of a drug can be therefore decreased [149,152]. In addition, it is important to explore how patient satisfaction due to new delivery systems can be translated in real-life increased compliance, reduced treatment burden and better clinical outcomes.…”
Section: Comparative Efficacy Of Inhaled Antibiotics In Cf and Endpoimentioning
confidence: 98%
“…In the context of a clinical trial setting, the patients' adherence is generally high, whereas in the real-world, rates of adherence and persistence rates are much lower and the efficacy of a drug can be therefore decreased [149,152]. In addition, it is important to explore how patient satisfaction due to new delivery systems can be translated in real-life increased compliance, reduced treatment burden and better clinical outcomes.…”
Section: Comparative Efficacy Of Inhaled Antibiotics In Cf and Endpoimentioning
confidence: 98%
“…Whilst non-adherence to CF treatments is well-reported and linked to negative health outcomes [5][6][7][8][9] , adherence to IPC recommendations is less well-understood. Patient rates of avoiding contact with other people with CF are reported to be low (21%-27%), particularly in young adults 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Briesacher et al 18 demonstrated both a 60% decrease in the risk of hospitalization for people who were adherent to their treatment regimen and a relationship between low usage of chronic medications and increased exacerbations requiring intravenous therapy. Improving patient outcomes rests, in part, on increasing adherence to chronic therapies, and identifying reasons for non-adherence to treatment is important.…”
Section: Introductionmentioning
confidence: 99%